2010
DOI: 10.1007/s12237-010-9294-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Zooplankton Grazing and Nutrient Loading in the Occurrence of Harmful Cyanobacterial Blooms in Florida Bay, USA

Abstract: Florida Bay is Florida's (USA) largest estuary and has experienced harmful picocyanobacteria blooms for nearly two decades. While nutrient loading is the most commonly cited cause of algal blooms in Florida Bay, the role of zooplankton grazing pressure in bloom occurrence has not been considered. For this study, the spatial and temporal dynamics of cyanobacteria blooms, the microbial food web, microzooplankton and mesozooplankton grazing rates of picoplankton, and the effects of nutrients on plankton groups in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…Cyano bacterial blooms in Florida Bay, perhaps combined with other environmental factors, seem to have disrupted pelagic (Goleski et al 2010) and possibly benthic (Peterson et al 2006) grazing in Florida Bay. Peterson et al (2006) found that sponge mortality in the north-central region of Florida Bay increased water column turnover time by sponge filtration from 3 d to 15 d, and this region of Florida Bay has experienced the most dense and persistent cyanobacterial blooms (Phlips et al 1999, Goleski et al 2010. To date, no study has considered how in situ changes in cyanobacteria blooms affect sponge populations in Florida Bay.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 3 more Smart Citations
“…Cyano bacterial blooms in Florida Bay, perhaps combined with other environmental factors, seem to have disrupted pelagic (Goleski et al 2010) and possibly benthic (Peterson et al 2006) grazing in Florida Bay. Peterson et al (2006) found that sponge mortality in the north-central region of Florida Bay increased water column turnover time by sponge filtration from 3 d to 15 d, and this region of Florida Bay has experienced the most dense and persistent cyanobacterial blooms (Phlips et al 1999, Goleski et al 2010. To date, no study has considered how in situ changes in cyanobacteria blooms affect sponge populations in Florida Bay.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…This correlation analysis was performed once with all sites and time-points pooled, and again with the data separated by time-point to avoid temporal pseudoreplication. A 'bloom threshold' of 350 × 10 3 cyanobacterial cells ml −1 (Phlips et al 1999, Goleski et al 2010) was used to classify each site at each time point as 'bloom' or 'non-bloom.' Cyanobacteria densities during intervals between time-points were modeled as simple exponential growth or decline, and these modeled densities were used to classify the intervals between time-points as 'bloom' or 'non-bloom.…”
Section: Measurements Of Cyanobacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Various physicochemical factors, biotic effects and hydro-meteorological characteristics have been assumed to be main reasons for cyanobacterial blooms (Paerl et al, 2001;Jin and Wang, 2006;Jiang et al, 2008;Goleski et al, 2010;Wang et al, 2011a). Many models have been developed to predict the dynamics of cyanobacterial blooms.…”
Section: Introductionmentioning
confidence: 99%